Effect of Japanese Kampo Medicine Therapy for Menopausal Symptoms after Treatment of Gynecological Malignancy - Akihiko Yoshimura; Kenjiro Sawada; Tomoyuki Sasano; Hiromasa Kuroda; Katsumi Kozasa; Erika Nakatsuka; Koji Nakamura; Kae Hashimoto; Seiji Mabuchi; Tadashi Kimura (Obstetrics and Gynecology International)
Loss of ovarian function by the treatment for gynecological malignancy results in a drastic decrease of estrogen causing physical and mental symptoms. The purpose of this study is to evaluate the effect of Japanese Kampo Kamikihito (KKT) and Kamishoyosan (KSS) on menopausal symptoms in gynecological cancer patients. Patients who had menopausal symptoms after gynecologic malignancy treatment were enrolled and randomly divided into a KKT or a KSS group. Kupperman Menopausal Index (KI) questionnaires were obtained before tumor treatment, at baseline, and at 4 and 8 weeks. Changes in KI scores and severity of each symptom were evaluated. A total of 33 patients were enrolled: 18 in the KKT group and 15 in the KSS group. The KI scores significantly decreased at 4 and 8 weeks compared with baseline in both groups. Although no significant difference was found in change in KI scores between the KKT and KSS groups, efficacy showed some differences. Both KKT and KSS were effective for insomnia, vertigo, and palpitation. KSS was also effective for vasomotor symptoms and arthralgia/myalgia. In conclusion, both KKT and KSS were effective for menopausal symptoms in patients after gynecological tumor treatment. Tailor-made Kampo therapy may contribute to improve patients’ physical and mental symptoms.